2009
DOI: 10.1303/aez.2009.587
|View full text |Cite
|
Sign up to set email alerts
|

Effects of artificial selection for reduced flight ability on survival rate and fecundity of Harmonia axyridis (Pallas) (Coleoptera: Coccinellidae)

Abstract: The effects of artificial selection for reduced flight ability on the survival rate and fecundity of the ladybird beetle Harmonia axyridis were assessed. The hatching rate, emergence rate and fecundity of the flightless strain were significantly lower than the control in the 36th generation after artificial selection was started under laboratory conditions. In greenhouses containing cultivated eggplant in which the flightless strain was released, the incidence of fourth instar larvae, i.e., offspring of releas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…One such study was conducted in Japan by Seko et al (2008), who found both longer residence times of a flightless strain of the ladybird beetle Harmonia axyridis in field plots of eggplant than by a flighted control group, and greater control of the target prey, Aphis gossypii by the flightless beetles. However, the inbreeding regimen used to provide the flightless beetles in this study led to some fitness declines (Seko and Miura 2009). Lommen et al (2008) have suggested taking advantage of natural variation in flight ability to overcome this problem.…”
Section: Too Much Dispersalmentioning
confidence: 86%
“…One such study was conducted in Japan by Seko et al (2008), who found both longer residence times of a flightless strain of the ladybird beetle Harmonia axyridis in field plots of eggplant than by a flighted control group, and greater control of the target prey, Aphis gossypii by the flightless beetles. However, the inbreeding regimen used to provide the flightless beetles in this study led to some fitness declines (Seko and Miura 2009). Lommen et al (2008) have suggested taking advantage of natural variation in flight ability to overcome this problem.…”
Section: Too Much Dispersalmentioning
confidence: 86%
“…Finally, we investigated whether the release of flightless H. axyridis reduced aphid damage on plants of a non-heading Brassica cultivar. Adults (\seven days old) and second instars of the flightless strain of Harmonia axyridis were provided from the stock culture of Agrisect (Tokyo, Japan) that was originally established by artificial selection for reduced flight ability at the National Agricultural Research Center for the Western Region of Japan (Seko and Miura 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Ueno et al Early fecundity (expressed as no. eggs per female) was measured over the first ten days after the onset of oviposition Data of line A and control 1 were from a previously published study (Seko and Miura 2009) Values within a column followed by different letters are significantly different (P \ 0.05) Assessment of hybrid vigor 89 (2004) suggested that the wingless gene has strong negative pleiotropic effects on certain fitness components in A. bipunctata. Hybridization should be effective to reduce the loss of fitness by inbreeding depression, but not be effective to reduce fitness loss due to pleiotropic effects.…”
Section: Discussionmentioning
confidence: 99%
“…These experiments were conducted under LD 16:8 at 25°C and 40-60% RH. The data of the isofemale line A (except the flight distance) and control 1 were taken from Seko et al (2008) and Seko and Miura (2009). …”
Section: Measurement Of Life-history Traits and Flight Performance Ofmentioning
confidence: 99%
See 1 more Smart Citation